MENINGKATAN KETERAMPILAN LOMPAT JAUH GAYA JONGKOK MELALUI MODIFIKASI ALAT BANTU - Widiastuti Widiastuti; Pramudito Hutumo (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2018)
This study attempts to improve learning outcomes the long jump style squat through modification learning tool .Of research in SMAN 1 Kotagajah Lampung .Research methodology used is research methodology the act of (action research) . technic the data such quantitative data and qualitative .This research result of the study results the long jump style squat through a learning modification .Increased is evident from the test rata-rata students , to test = 73.09 early , and then students tests showed a rise in cycle i = 80,84 .To learn students graduation the results of a pretest long jump students who passed a number of 9 students ( 36 % ) , cycles i students who passed a number of 25 students ( 100 % ) instrument tests for research has been tested reliability , with the r = 0,84 .According to Suharsimi Arikunto ( 2006 ) , the r = 0.84 can be said this instrument high reliability.